Analyzing Errors In Recount Text Written By The Third Year Students Of SMAN 1 Pinrang - Hardiani Ardin (JIKAP PGSD: Jurnal Ilmiah Ilmu Kependidikan, 2017)
This research aimed to find out the most frequent errors that the students made in writing recount text. This research used descriptive method with quantitative data analysis technique to answer the proposed question. The scope of the research was limited to the grammatical analysis and the mechanics of writing components to the forty recount texts written by the third year students of SMAN 1 Pinrang. The errors were classified into nine categories: errors in using verb form; subject-verb agreement; the use of article; the use of preposition; noun pluralization; the use of pronoun; the use of conjunction; spelling and punctuation. There were 704 errors that the researcher found. The research findings indicated that the most frequent errors made by the students were in using verb form, punctuation, preposition, spelling, noun, article, and pronoun. It could be inferred that the students have not mastered the grammar well. They face a lot of problems in English language generally and particularly in writing the English language.